PEMBINAAN PENULISAN KARYA TULIS ILMIAH MELALUI SIKLUS DEMING (DEMING CYCLE) DI SEKOLAH BINA GUNA MENINGKATKAN KARIR DAN PROFESIONALISME GURU - Jamalludin Jamalludin (STAI Sangatta Kutai Timur, 2022)
This research is educational policy research in schools with the aim of fostering scientific writing to improve the career and professionalism of teachers in foster schools. This research was carried out in five (5) development schools consisting of SMP Negeri 2 Sangatta Utara, SMP Negeri 4 Muara Bengkal, SMP Negeri 4 Sandaran, and SMP Negeri 5 Sandaran for the academic year 2021/2022, with the research subjects of 30 teachers and objects research on the development of teaching scientific writing.The methodology used in this study is to use the Deming Cycle (plant, do, control, action). The findings of the research on the development of scientific writings for teachers in foster schools with the following components: (1) plans for writingscientific papers in the professional development of teachers in foster schools have gone very well, with 95% of activity plans running according to indicators (2) plans implementation of teacher scientific writing developmentwith in-house training 90% went very well, (3) the results of the implementation of teacher scientific writing development had compiled scientific papers as many as 23 teachers or about 76%, (4) followup results went well. good, 7 teachers, or 23% of teachers are continuously trained to improve teacher career development.The conclusion of this study is that there is an increase in the development of scientific writing for teachers in foster schools, teachers innovate following self-development according to their competencies according their era.